2011
DOI: 10.1371/journal.pone.0017454
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Human Muscle-Derived Cells to Skeletal Muscle Regeneration in Dystrophic Host Mice

Abstract: BackgroundStem cell transplantation is a promising potential therapy for muscular dystrophies, but for this purpose, the cells need to be systemically-deliverable, give rise to many muscle fibres and functionally reconstitute the satellite cell niche in the majority of the patient's skeletal muscles. Human skeletal muscle-derived pericytes have been shown to form muscle fibres after intra-arterial transplantation in dystrophin-deficient host mice. Our aim was to replicate and extend these promising findings.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 61 publications
2
79
0
Order By: Relevance
“…Endothelial and haematopoietic cells do not give rise to adipocytes (Berry and Rodeheffer, 2013), and our cell counts showed that the CD56 2 / TE-7 2 population of cells (which might include these cells) is also far too small to account for the number of adipocytes observed in our cultures. The non-adherent nature of some of these cell types also ensures they would have been discarded before obtaining the sorted cells -this applies to the 'small refractory' cell population identified by Meng and co-workers (Meng et al, 2011), the 'muscle-derived stem cells' (Lee et al, 2000;Qu-Petersen et al, 2002) and the pericytes identified in human muscle by Dellavalle and colleagues (Dellavalle et al, 2011). The small refractory cells (Meng et al, 2011) were initially both CD56 2 and non-adherent; only after 14 days in culture and when provided with collagen-I substrate were they able to adhere, and eventually gave rise to some CD56 + cells.…”
Section: Cd56mentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial and haematopoietic cells do not give rise to adipocytes (Berry and Rodeheffer, 2013), and our cell counts showed that the CD56 2 / TE-7 2 population of cells (which might include these cells) is also far too small to account for the number of adipocytes observed in our cultures. The non-adherent nature of some of these cell types also ensures they would have been discarded before obtaining the sorted cells -this applies to the 'small refractory' cell population identified by Meng and co-workers (Meng et al, 2011), the 'muscle-derived stem cells' (Lee et al, 2000;Qu-Petersen et al, 2002) and the pericytes identified in human muscle by Dellavalle and colleagues (Dellavalle et al, 2011). The small refractory cells (Meng et al, 2011) were initially both CD56 2 and non-adherent; only after 14 days in culture and when provided with collagen-I substrate were they able to adhere, and eventually gave rise to some CD56 + cells.…”
Section: Cd56mentioning
confidence: 99%
“…The non-adherent nature of some of these cell types also ensures they would have been discarded before obtaining the sorted cells -this applies to the 'small refractory' cell population identified by Meng and co-workers (Meng et al, 2011), the 'muscle-derived stem cells' (Lee et al, 2000;Qu-Petersen et al, 2002) and the pericytes identified in human muscle by Dellavalle and colleagues (Dellavalle et al, 2011). The small refractory cells (Meng et al, 2011) were initially both CD56 2 and non-adherent; only after 14 days in culture and when provided with collagen-I substrate were they able to adhere, and eventually gave rise to some CD56 + cells. The 'muscle-derived stem cells' obtained by Lee and co-workers (Lee et al, 2000), could only be obtained by repeated subculturing of non-adherent cells, and the CD56 2 'pericytes' with multi-lineage potential that were identified in human muscle (Dellavalle et al, 2011) are also a small fraction (estimated at about 2-4% of the isolated cell population).…”
Section: Cd56mentioning
confidence: 99%
“…within muscle fibers and/or satellite cells. But CD56 -or non-sorted cells contributed to significantly more nuclei outside the basal lamina, confirming that there were more non-myogenic cells within CD56 -cell population (Meng et al, 2011b). Zheng et al showed that human skeletal muscle-derived CD56 + cells that also expressed CD34 and CD144 (myoendothelial cells) contributed to more muscle regeneration than did CD56 + /CD34 -/CD144 -cells (myoblasts) (Zheng et al, 2007) in contrast to the findings of Meng suggesting that pericytes, rather than endothelial cells, are the major CD56 -contributor to muscle regeneration (Meng et al, 2011b) …”
Section: Contribution Of Locally-delivered Donor Stem Cells To Musclementioning
confidence: 69%
“…However, when grafting cells from one donor to another, the host must either be immunodeficient or immunosuppressed. Therefore, mdx mice with different types of immunodeficiency have been used as hosts in cell transplantation experiments, including mdx nu/nu (Boldrin et al, 2009;Collins et al, 2005;Partridge et al, 1989), SCID mdx (Benchaouir et al, 2007;Dellavalle et al, 2007;Torrente et al, 2004), Rag -/-mdx (Gerard et al, 2011), or mdx mice immunosuppressed with FK506 (Kinoshita et al, 1994b), but to what extent these different hosts are comparable, being on different genetic backgrounds and having different mechanisms and degrees of immunodeficiency, has not been ascertained (reviewed (Meng et al, 2011b)). Immunodeficient mice are more convenient to work with than mice that have to be immunosuppressed and seem to permit greater donor-myoblast-derived muscle regeneration (Partridge et al, 1989).…”
Section: Models and Markersmentioning
confidence: 99%
See 1 more Smart Citation